Pengaruh Brand Ambassador dan Brand Awareness terhadap Keputusan Pembelian Snack Tos Tos Tortilla Chips pada Penggemar NCT Dream di Jakarta Barat - Shefira Eka Jasutania; Henny Armaniah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In the increasingly competitive snack food industry, companies need effective marketing strategies to attract consumer attention. One commonly used strategy is utilizing Brand Ambassadors and enhancing Brand Awareness to build a positive brand image in the minds of consumers. PT Dua Kelinci, as the producer of Tos Tos Tortilla Chips, has adopted this approach by collaborating with the South Korean idol group NCT Dream as its Brand Ambassador to expand market reach and attract K-pop fans in Indonesia. The problem in this research lies in the lack of understanding regarding the extent to which Brand Ambassador and Brand Awareness influence purchasing decisions. This study aims to determine the effect of Brand Ambassador and Brand Awareness on purchasing decisions of Tos Tos Tortilla Chips among NCT Dream fans in West Jakarta. The research method used is a quantitative approach through the distribution of questionnaires and analysis using data quality testing and multiple linear regression. The results show that both variables, Brand Ambassador and Brand Awareness, have a positive and significant influence, both partially and simultaneously, on purchasing decisions. This indicates that selecting the right public figure and maintaining a high level of Brand Awareness can increase consumer interest and purchasing decisions.